Disclosing Corporate Social Responsibility Affects Company Value: Profitability as Moderating Variable - Candra, Anastasya Regina; Tanison, Nindy; Martusa, Riki; Meythi, Meythi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
The goal of this research is to determine how company value is impacted by corporate social responsibility (CSR) and how profitability, as determined by the rate of return on assets (ROA), modifies this impact. The main reason is that businesses which can disclose their CSR will garner greater public attention. Purposive sampling was employed in this study, consisting of all businesses listed on the Indonesia Stock Exchange (IDX) during 2018 to 2022. Because relatively few organizations are prepared to participate in CSR due to the significant expenditures involved, the paper’s findings show that CSR Disclosure does not significantly affect company value. The second finding stated that profitability as defined by return on assets (ROAt) can enhance the interaction among CSR disclosure and company value because profitable businesses can afford to make larger investment in CSR, which can best serve stakeholders who are essential to the business’s longevity.